Artful dodgers : reconceiving the golden age of children's literature - Gubar, Marah, 1973- (Oxford ; New York : Oxford University Press, 2009)
"In this contribution to Victorian and children's literature studies, Marah Gubar proposes a fundamental reconception of the nineteenth-century attitude toward childhood. The ideal and ideology of innocence was much slower to spread than we think, she contends, and the people whom we assume were most committed to it - children's authors and members of the infamous "cult of the child" - were in fact deeply ambivalent about this Romantic notion." "In the process of tracing how Golden Age authors explored the enigmatic issue of the child's agency, Gubar offers a new account of the rise of the child narrator, the vogue for child actors, and the emergence of children's theatre. Artful Dodgers is essential reading for anyone interested in literary and dramatic representations of children."--BOOK JACKET.
Our field: the rise of the child narrator -- Collaborating with the enemy: Treasure Island -- Reciprocal aggression: unromantic agency in the art of Lewis Carroll -- Partners in crime: E. Nesbit and the art of thieving -- The cult of the child and the controversy over child actors -- Burnett, Barrie, and the emergence of children's theatre.
Includes bibliographical references (p. 233-251) and index.
Keywords: Children's literature, English -- History and criticism; English literature -- 19th century -- History and criticism; Children in literature; Adolescence in literature